Konsep Guru Sebagai Profesi - Bakhrudin All Habsy; Anggun April Seli Ivonesa; Islami, Ilmi Fitri Islami; Mayse Shaella Yusel (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education is a necessity for everyone, therefore the government must guarantee all its citizens to get a proper education. The challenges in implementing the provisions and regulations of the education sector are enormous. With technological advances, mastery of technology in education is also needed. Education is used as the key to improving the quality of the nation, the progress of a nation is determined by the younger generation who will be the successor of the nation. A quality young generation is produced from a quality education. The teacher profession is important in improving education, because it is tasked with teaching, educating, fostering, and shaping personalities so that they become human beings who have knowledge, are intelligent, and dignified. A profession is a job or position that must have special expertise, responsibility and mastery of knowledge in that field. To obtain professional certification, teachers need professional requirements obtained through special education so that they can produce professional teachers. The purpose of this research is to describe the concept of teachers as a profession in Indonesia. The method used in this research is qualitative with literature review method. The results of this study show (1) The meaning of the profession (2) Teachers as a profession (3) Professional organizations of teachers (4) The role of teachers (5) Expertise, qualifications and competencies of teachers (6) Professional skills of teachers (7) Teachers' code of ethics and standards (8) Teachers' professional status (9) Responsibilities, laws and administration.